IMPLEMENTASI PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MEMAHAMKAN ASKING AND GIVING INFORMATION PADA SISWA SEKOLAH MENENGAH PERTAMA: SMP NEGERI 2 BONDOWOSO - JUMARTO (Dewan Pendidikan Bondowoso, 2021)
The current condition of Indonesia is so alarming, the emergence of Covid-19. This has caused the paralysis of various sectors, one of which is education. For this reason, the policy to answer these challenges is one of them with limited face-to-face learning (PTMT). PTMT must still involve students to be active in learning. Learning that gives active learners to build knowledge of English in a meaningful way can be realized in cooperative learning. The simplest cooperative learning is the Student Teams Achievement Divisions (STAD) type of cooperative learning. This research uses a qualitative approach with the type of research used is classroom action research (CAR) one cycle. The action implementation activity was carried out 8th grade of SMP Negeri 2 Bondowoso in the English subject of asking and giving information. The stages of implementing the action are in accordance with the STAD-type cooperative learning stages which include introduction, group learning, individual tests and group rewards. The results of this study are the implementation of STAD type cooperative learning has been carried out well according to the syntax and steps of STAD cooperative learning although there are some technical obstacles.